PERANCANGAN DESAIN UI/UX APLIKASI LOWONGAN PEKERJAAN MENGGUNAKAN METODE GOAL DIRECTED DESIGN - Pangiawan, Harfandy Putra; Arianti, Arianti; Musdar, Izmy Alwiah (JTRISTE, 2023)
This research aims to design the UI/UX for a job vacancy application using the Goal Directed Design method. Data collection was conducted with 20 respondents who had used the Hi Jobs application, and the data was processed using the System Usability Scale (SUS). Based on the first evaluation using the System Usability Scale (SUS) questionnaire, the average score was 33.5, with Acceptability Ranges receiving the label "Not Acceptable," Grade Scales falling into the "F" category, and Adjective Ratings categorized as "Poor." This indicates deficiencies in the user interface design of the Hi Jobs application, both in appearance and features, and it did not meet the standard System Usability Scale (SUS) score of 68.After making improvements to the Hi Jobs application, a final evaluation was conducted using the System Usability Scale (SUS), resulting in an average score of 77. The Acceptability Ranges received the label "Acceptable," Grade Scales were in the "C" category, and Adjective Ratings were categorized as "Good." The findings of this research indicate that the Hi Jobs application, with its UI/UX design focusing on user needs and goals, allows job seekers and employers to interact easily and efficiently. This research contributes positively to the development of job vacancy applications with a focus on satisfying user experiences.